Characterizing pre-discharge interventions to reduce length of stay for older adults: A scoping review - Emily Garcia; Zachary J. Hass (PLoS ONE, 2025)
Background Hospital pre-discharge interventions are becoming one of the leading strategies to promote early discharge. For older adult patients, it remains unclear what these interventions are and how they affect discharge outcomes. Objective This scoping review categorizes pre-discharge interventions promoting early acute care hospital discharging or total hospital length of stay reductions among older adults, synthesizes contextual factors (e.g., cost, staffing) driving implementation, and assesses the perceived intervention’s impact. Design The review followed the five states of the Arksey and O’Malley framework and the PRISMA-ScR extension. The PubMed, Embase, and Scopus databases were searched from 1983 to 2020 for pre-discharge interventions designed or adapted to discharge older adults earlier in their stay from acute care hospitals. Potentially relevant articles were screened against eligibility criteria. Findings were extracted and collated in data charting forms followed by brief thematic analyses. Results The search yielded 5,455 articles of which 91 articles were included. Eight pre-discharge intervention categories were identified: clinical management, diagnostic/risk assessment tools, staffing enhancements, drug administration, length of stay protocols, nutrition planning, and communication improvements. Leading motivations for intervention implementation included the nationwide drive to reduce care costs and hospitals’ need to increase hospital profitability, improve quality of care, or optimize resource utilization. Discharge outcomes reported included hospitalization costs, readmission rates, mortality rates, resource utilization rates and costs, and length of stay. Mixed results were found regarding the effectiveness of early discharge interventions on discharge outcomes based on expressed author sentiment. Conclusions The drive for pre-discharge interventions that reduce older adult hospital stays and associated costs continues to stem primarily from economic and governmental policies. Follow-up studies may be required to emphasize patient perspectives and care trajectories to avoid unintentional costly and health-deteriorating consequences.